Evaluation of Postoperative Hearing Outcome and Recurrence for Pars Flaccida Cholesteatoma. (23rd August 2013) - Hoshi, Yujiro; Kashio, Akinori; Karino, Shotaro; Sakamoto, Takashi; Kakigi, Akinobu; Iwasaki, Shinichi; Yamasoba, Tatsuya
Abstract : Objectives: Find out which factors affect postoperative hearing outcomes and those which affect recurrence rate in cases of pars flaccida cholesteatoma. Methods: Fifty‐six ears of 54 patients who underwent tympanoplasty for pars flaccida cholesteatoma for the first time at our hospital between 2006 and 2011 were enrolled. Progression of cholesteatoma, results of postoperative hearing, and the incidence of recurrence were compared. To define the progression of cholesteatoma, we used components of the classification proposed by American Academy of Otolaryngology—Head and Neck Surgery (AAO‐HNS) and the Japan Otological Society. Results: Cholesteatoma was present in eustachian tube, protympanum, or both in 13 cases, in the mesotympanum in 36, and in the mastoid cavity in 39. The stapes was intact in 47 cases, in which mucosa surrounding the stapes was normal in 15 and granulation tissue and/or cholesteatoma were present adjacent to the stapes in 32. Stapes superstructures were (nearly) completely destroyed in 8, and the stapes was not observed in one. Hearing was improved in 39 cases, with no significant difference in postoperative hearing among the regions involved by cholesteatoma. The cholesteatoma recurred in 5 cases. Recurrence was significantly more frequent when cholesteatoma involved the eustachian tube and/or protympanum ( P = 0.041) and also when the stapes was destroyed ( P = 0.043). Conclusions: Progression into the eustachian tube and/or protympanum and the destruction of the stapes superstructure are considered important factors to predict postoperative recurrence of pars flaccid cholesteatoma.